The electrochemical detection of arsenic(III) at a silver electrode - Simm, A; Banks, C; Compton, R (2005)
A study of three electrode substrates namely gold, platinum and silver, for arsenic detection via anodic stripping voltammetry is reported. Hitherto it has been accepted that gold is the most suitable metallic surface for use in this context, as suggested by Forsberg and co-workers (Forsberg, G.; O'Laughlin, J. W.; Megargle, R. G. Anal. Chem. 1975, 47, 1586.). We revisit these experiments and find that by switching from hydrochloric acid to nitric acid the oxidation of silver that had previously masked the arsenic stripping signal at this surface is shifted considerably enough to allow a clear, analytically reliable As(III) stripping signal to be detected. In contrast to silver and gold platinum is found to have poor performance as an electrode substrate for arsenic detection. Using ASV a LOD of 6.3 × 10-7 M is found for As(III) detection at a silver electrode, similar to that which we have previously reported at a gold electrode (A. O. Simm, C. E. Banks and R. G. Compton. Electroanalysis, 2005, 17, 335.) The use of ultrasound was then investigated to further reduce the LOD, which was found to be 1.4 × 10-8 M. Apart from reduced cost of silver it also has an added advantage over gold in that it has a higher hydrogen reduction overvoltage enabling a 100 mV more negative deposition potential to be used before the onset of hydrogen evolution when compared to a gold electrode. © 2005 Wiley-VCH Verlag GmbH and Co. KGaA.